Early detection of drought stress in grass swards with imaging spectroscopy - Schut, Antonius; Ketelaars, J. (Elsevier, 2003)
The potential of an experimental imaging spectroscopy system with high spatial (0.28-1.45 mm2) andspectral (5-13 nm) resolution was explored for early detection of drought stress in grass. A climate chamber experiment was conducted with nine Lolium perenne L. mini swards with drought stress treatments at two nitrogen levels. Images were recorded once every two days. Growth was monitored by changes in ground cover (GC), index of reflection intensity (IRI) and wavelength position of and gradient at inflection points, as estimated from images. Drought stress increased leaf dry matter and sugar content. Drought stress decelerated and ultimately reversed GC evolution, and kept IRI at low values. In contrast to unstressed growth, all absorption features narrowed and became shallower under drought stress. The inflection points near 1390 and 1500 nm were most sensitive to drought stress. Differences between drought stress and control swards were detected shortly before leaf water content dropped below 80%. The evolution of inflection point wavelength positions reversed under drought stress, except for the inflection point at the red edge where the shift to longer wavelengths during growth accelerated. The relation between inflection points at 705 and 1390 nm differentiated unstressed swards at an early growth stage from drought-stressed swards in a later growth stage.